Data's role in attracting foreign internationalization efforts. A comparative study between emerging and developed economies: go-to-market strategy for siemens healthineers workforce solution products in South Africa - Senoner, Matteo (2022)
Internationalization presents considerable challenges to companies, under diverse, and different conditions from their home country. As such, more information is needed to understand new markets. Hence, does a lack of publicly available data hinder emerging countries to attract foreign investment? To answer this, a comparative study on the internationalization of a major medical equipment manufacturer was conducted between South Africa and Germany. It determined that lack of data reduces the likelihood of foreign investment in a country. To alleviate this, public authorities are encouraged to make specific information on market conditions publicly available and to update them on a regular basis.